Our Experience in Treatment Acute Surgical Diseases of the Abdominal Cavity in Patients with Situs Inversus Viscerum (Transposition of Internal Organs) - S.R. Baymakov1, S.Sh. Yunusov2, U.R. Jamilov3, Sh.Kh. Bobokulov4, Sh.Sh. Boltaev5, Sh.Sh. Jonibekov6 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Situs viscerumtotalis is a fairly uncommon anomaly of the mirror-imaged arrangement of the peritonealcavity organs with a frequency of distribution in the range from 1: 5000 to 1: 20 000. Such an arrangementof internal organs is found in one case per 10 million2. In the early embryonic stage, the internal organs arelocated along the midline of the body. Normally, in the course of their subsequent development, they growand rotate to the right, and – exceptionally rarely – to the left, which leads to the reverse arrangement ofinternal organs, i.e., to their transposition. In the case of complete (total) transposition of internal organs, allof them are inverted. In the case of partial transposition, it involves inversion of all or some organs of oneof the body cavities (heart, stomach, duodenum and caecum, spleen). Dextrocardia, a condition in which thecardiac apex is pointed to the right, was first described by Marco Severino, in 1643. Matthew Baillie firstdescribed situs inversus more than a century later.